REFLEKSI KEPEMIMPINAN KRISIS PEMERINTAH PADA FASE AWAL COVID-19 DI INDONESIA - Frederik Masri Gasa; Herma Retno Prabayanti; Yosephine Aurelia Purnomo (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study uses a qualitative approach that aims to examine the government's crisis leadership during the early period of the COVID-19 pandemic in Indonesia. The COVID-19 pandemic is a crisis that requires appropriate and fast handling from the government as a leader. Leaders must have crisis leadership characteristics in order to get out of crisis situations. The unit of analysis for this research is the December 2, 2020 edition of Kompas.com, entitled “9 Bulan Pandemi Covid-19, Apa yang Salah dengan Penanganan di Indonesia.” Through this news, Kompas.com media is trying to evaluate the government's performance in dealing with COVID-19 in Indonesia. The news text is analyzed using Robert N. Entman's framing analysis model as a data analysis method, which consists of four main elements, namely define problems, diagnose cause, make moral judgment and treatment recommendation. The results show that the three indicators described in the news illustrate that from March to December 2020, the government is considered not to have the characteristics of a crisis leader, namely being responsive, implementing performance management (rewards and consequences) and having good articulation in conveying communication.